Twitter influential users ranking using Twitter user characteristics - Saikaew, Kanda Runapongsa; Krutkam, Wit (Engineering and Applied Science Research, 2015)
Social media sites have experienced an explosion in both the number of users and the amount of user-contributed content in recent years. There is the need for the solution for information overload in social media. In this paper, we focus on solving the problem of finding relevant Twitter users to follow and selecting only popular tweets to post, we have collected information about Twitter users, particularly the number of influential users who are followers, the number of general followers, and the number of tweets that are frequently retweeted. Then we used such statistics information to compute the user rankings. In addition, we also created a Twitter account to automatically post only tweets that have been retweeted many times. Based on the survey result and using the Spearman’s rank correlation coefficient, the recommended Twitter users suggested by the system have proven to be popular and pertinent, and the rank order by the proposed system has a statistical significant degree of similarity with the user survey result.